L'aspecte pedagògic de Carles Salvador - Quixal San-Abdon, Josep M. (Caplletra. Revista Internacional de Filologia, 2015)
This article deals with the educational background of Carles Salvador, first with his studies at the Escola Normal, followed by lectures and experiences which would guide his professional development, to the degraded situation as a high school teacher of the Spanish State.